1992
DOI: 10.2105/ajph.82.2.180
|View full text |Cite
|
Sign up to set email alerts
|

A cost-effectiveness analysis of three staffing models for the delivery of low-risk prenatal care.

Abstract: BACKGROUND. Health care costs are increasing at more than twice the rate of inflation, thus, public officials are seeking safe and economic methods to deliver quality prenatal care to poor pregnant women. This study was undertaken to determine the relationship between the cost and effectiveness of three prenatal clinic staffing models: physician based, mixed staffing, and clinical nurse specialist with physicians available for consultation. METHODS. Maternal and neonatal physiological outcome data were obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 9 publications
1
22
0
Order By: Relevance
“…These concerns are congruent with findings from other research (Graveley & Littlefield, 1992;Olivo, Freda, Piening, & Henderson, 1994;Welch, 1996) in which it has been found that women prefer female providers who they find more understanding and knowledgeable, especially in regard to women's problems. For many low-income women and children, the health care system itself can be perceived as a barrier, as access to health care can be foiled by inflexible office hours that do not accommodate working mothers and school-age children (Ahmed & Maurana, 1999;Salganicoff & Wyn, 1999), and having to spend more than the usual time waiting at clinics is a common dissatisfaction (Riportella-Muller et al, 1996;Salganicoff & Wyn, 1999;Stevenson et al, 1994).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These concerns are congruent with findings from other research (Graveley & Littlefield, 1992;Olivo, Freda, Piening, & Henderson, 1994;Welch, 1996) in which it has been found that women prefer female providers who they find more understanding and knowledgeable, especially in regard to women's problems. For many low-income women and children, the health care system itself can be perceived as a barrier, as access to health care can be foiled by inflexible office hours that do not accommodate working mothers and school-age children (Ahmed & Maurana, 1999;Salganicoff & Wyn, 1999), and having to spend more than the usual time waiting at clinics is a common dissatisfaction (Riportella-Muller et al, 1996;Salganicoff & Wyn, 1999;Stevenson et al, 1994).…”
Section: Discussionsupporting
confidence: 88%
“…There is ample support for nurse managed clinics with numerous reports documenting cost effectiveness and client satisfaction with primary health care received from NPs, nurse midwives, and advanced practice nurses (Bear & Bowers, 1998;Brown & Grimes, 1995;Chang et al, 1999;Graveley & Littlefield, 1992;Ramsey, Edwards, Lenz, Odom, & Brown, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, 20 references to the measurement of maternal satisfaction were identified and included in the analysis: Astbury et al , 1994; 13 Bramadat and Driedger, 1993; 14 Brown and Lumley, 1994; 15 Cottrell and Grubbs, 1994; 16 Drew et al , 1989; 17 Flint et al , 1989; 18 Giles et al , 1992; 19 Graveley and Littlefield, 1992; 20 Green et al , 1990; 21 Hambly, 1997; 22 Higgins et al , 1994; 23 Hornberger et al 1996; 24 Jacoby, 1987; 25 Kenny et al , 1993; 26 Matthews, 1991; 27 Righard et al , 1993; 28 Rowley et al , 1995; 29 Seguin et al , 1989; 30 Small et al , 1992; 31 and Waldenstrom and Nilsson, 1993 32 …”
Section: Methodsmentioning
confidence: 99%
“…Of the 9470 charts examined by the abstractors, 4431 (46.8%) met the eligibility criteria (Table 1); random-number tables were used to randomly select 11 charts from each provider's practice for inclusion in the study. Providers who had fewer than 11 eligible charts during the study year had all their eligible charts abstracted.…”
Section: Selection Ofpatient Sample and Data Collectedmentioning
confidence: 99%